Determinants of Foreign Direct Investment in Five ASEAN Countries - Dwika, Dwika Murti Anggraini (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
This research is entitled “Determinants of Foreign Direct Investment in Five ASEAN Countries. This study aims to see the development of foreign investment in five ASEAN countries in 2005-2021 and to measure and analyze the effect of the variables GDP, government spending, exchange rates, and foreign debt on foreign investment in five ASEAN countries 2005-2021 years. The research method used in this study is descriptive analysis and quantitative analysis using panel data analysis tools using data for 2005-2021. The research results reveal that the development of foreign investment in five ASEAN countries during the 2005-2021 period has fluctuated every year and GDP and foreign debt have a positive and significant effect on foreign investment in the five ASEAN countries. Meanwhile, government spending and exchange rates have no effect on foreign investment in the five ASEAN countries.